Frontispiece: Entropy‐Driven Diastereoselectivity Improvement in the Paternò–Büchi Reaction of 1‐Naphthyl Aryl Ethenes with a Chiral Cyanobenzoate through Remote Alkylation. Issue 18 (17th April 2018) - Nagasaki, Keisuke; Inoue, Yoshihisa; Mori, Tadashi
Abstract : Photochemistry In their Communication onpage 4880 ff., T. Mori et al. highlight the critical role of entropy in determining the diastereoselectivity of Paternò–Büchi reactions of 1‐naphthyl aryl ethenes with a chiral 4‐cyanobenzoate.